Cross-border labour mobility within an enlarged EU - Frigyes Ferdinand Heinz; Melanie Ward-Warmedinger (European Central Bank (ECB), 2006)
This paper examines the potential for increased cross-border labour mobility within the EU-25 and considers the costs and benefits of any increase in labour mobility to both sending and receiving countries in the medium to long run. Evidence from previous EU enlargement experiences, academic studies, the existence of barriers to mobility within the EU and the economic determinants of migration all indicate a moderate potential for increased migrant flows. The magnitude of cross-border labour flow in the medium to long run will most likely be largely a function of the demand for migrants and the speed at which the EU-8 catches up economically with the EU-15. If broad-based economic growth and social development continues in the EU-8, labour migration will most likely decrease. In addition, faster population ageing in the EU-8 tends towards dampening migration flow from the new Member States in the medium term. In terms of costs and benefits, for the EU-8 countries labour migration, especially in the short run, may present a number of challenges. Emigration may tend to weigh disproportionally on the pool of young and educated workers, aggravating labour market bottlenecks in a number of EU-8 countries. For the EU-25 as a whole, cross-border labour mobility is likely to offer a number of advantages, by allowing a more efficient matching of workers` skills with job vacancies and facilitating the general upskilling of European workforces. The current restrictions on labour mobility from the EU-8 countries to the other EU member countries stand in contrast with one of the central principles of the EU – the free movement of labour. Furthermore, these restrictions may decrease the efficient use of labour resources in the face of demographic change and globalisation and hamper an important adjustment mechanism within EMU. Delaying the removal of these barriers may be costly for the EU-25 at a time when leaders are concerned about Europe`s international competitiveness and may increase illegal work in a number of countries. Finally, it would not be beneficial for Europe to loose a significant part of the most agile and talented individuals from the new Member States to more traditional migration centres such as the US and Canada.
Keywords: 330; Regionale Arbeitsmobilität; EU-Staaten; EU-Mitgliedschaft